Role of Agile in Digital Public Health Transformation - Kokol, Peter; Blažun Vošner, Helena; Kokol, Marko; Završnik, Jernej (Frontiers in Public Health, 2022)
The digitalization of healthcare, fueled by advances in technology and Covid pandemic can not only empower equitable access to global expert-level healthcare, but also make health care more patient-centric. Every digital health solution has one common fundamental component; they all run on computing platforms and are powered by complex software. Traditional software development life cycles have often failed in designing complex software, consequently agile approach was introduced. To assess the role of agile in digital public health transformation we used the synthetic knowledge synthesis, a triangulation of bibliometric mapping and thematic analysis, to analyse the available literature harvested from PubMed, The analysis showed that the use of agile approach is underutilized in developing digital health software. Moreover, the study revealed that health organization did not yet embrace the agile culture and should adapt using innovative agile solutions to deliver clinical value to patients and public health systems. Following the software industry, where agile software development is becoming the mainstream approach also for sensitive and regulated software, it is becoming even more essential that the digital health software development process should be modernized. Furthermore, shift to Agile collaboration, Agile Decision-making, Trial tolerance, Active engagement, Purposeful technology adoption, Knowledge sharing and Open Agile innovation ecosystem must be achieved.